Country Boy : The Roots of Johnny Cash - Woodward, Colin Edward, 1975- (Book collections on Project MUSE., 2022)
"In Country Boy, Colin Woodward combines biography, social and political history, and music criticism to tell the story of Johnny Cash's time in his native Arkansas. Woodward explores how some of Cash's best songs are based on his experiences growing up in northeastern Arkansas, and he recounts that Cash often returned to his home state, where he played some of his most memorable and personal concerts"--